Digital Videoscopic Retrograde Intrarenal Surgeries for Renal Stones: Time-to-Maximal Stone Length Ratio Analysis - Jeong, Jae Yong; Kim, Jong Chan; Kang, Dong Hyuk; Lee, Joo Yong (Yonsei medical journal, 2018)
To investigate 100 consecutive cases of videoscopic retrograde intrarenal surgery (RIRS) by a single surgeon and to evaluate factors associated with stone-free status and the learning curve thereof. We analyzed the results of videoscopic RIRS in 100 patients who underwent primary treatment for renal stones from January 2015 to August 2016. Videoscopic RIRS were performed with URF-V and URF-V2 flexible video uteroscopes (Olympus) or a Flex-Xc flexible ureterorenoscope (KARL STORZ). Non-contrast computed tomography was taken at 3 months postoperatively to confirm the absence of stones. The stone characteristics included the location, maximal stone length (MSL), stone heterogeneity index (SHI), and mean stone density (MSD). Fragmentation efficacy was calculated as operative time (min) divided by removed MSL (mm), and was evaluated in the sequential order of operations. The mean age of the total patient was 60.0±14.0 years. The mean MSL was 13.1±6.2 mm. The average MSD was 734.2±327.6 Hounsfield unit (HU) and the SHI was 241.0±120.0 HU. The mean operation time was 65.1±45.7 min considering each renal unit. The stone-free rate at 3 months post-surgery was 87%. The estimated cut-off of the time-to-MSL ratio below 5 min/mm was 50. Multivariate analyses indicated a lower MSD [odds ratio (OR): 0.998; 95% confidence interval (CI): 0.996-0.999; p=0.047) and the last 50 cases (OR: 5.408, 95% CI: 1.337-30.426; p=0.030) as independent predictors of stone-free status after videoscopic RIRS. Low MSDs and the last 50 cases were significant predictors of stone-free rate in videoscopic RIRS.